Konsep Diri Anak Korban Kekerasan Seksual di Pusar Pelayanan Terpadu Jayandu Widuri Kabupaten Pemalang - Berliannanda, Anugrah Fitria; Maryami, Ami; Ningrum, Sri Ratna (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2024)
Sexual violence against children is a critical issue in Indonesia, with significant impacts on victims' physical and psychological development, especially their self-concept. This study explores the self-concept of child victims of sexual violence at the Jayandu Widuri Integrated Service Center, Pemalang Regency, focusing on the social dimension. Utilizing the Tennessee Self-Concept Scale (TSCS), this research analyzes how trauma disrupts victims' ability to build trust and interact socially. Findings reveal that victims often experience isolation, social stigma, and difficulties in establishing interpersonal relationships. These challenges underscore the need for effective interventions to rebuild their self-concept and reduce social stigma. The study employs a combination of quantitative and qualitative methods, including structured interviews and thematic analysis, to evaluate the effectiveness of Social Group Work interventions. Results indicate that group-based activities, such as peer support and social simulations, significantly improve victims' social skills and confidence. Additionally, family involvement plays a critical role in reinforcing emotional support and facilitating recovery. However, deep-seated trauma and societal stigma remain barriers to effective rehabilitation, highlighting the importance of creating a supportive and inclusive environment.This research emphasizes the necessity of a holistic approach in addressing the multifaceted impacts of sexual violence on children. By integrating psychological, social, and community-based interventions, the findings advocate for the expansion of community rehabilitation programs like those at Jayandu Widuri. These insights provide a foundation for developing more inclusive policies and practices to ensure the optimal recovery of child victims, allowing them to reintegrate into society with a renewed sense of self-worth and confidence.